2007
DOI: 10.1103/physrevlett.98.158102
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependence of the Collective Dynamics of Swimming Bacteria

Abstract: At concentrations near the maximum allowed by steric repulsion, swimming bacteria form a dynamical state exhibiting extended spatiotemporal coherence. The viscous fluid into which locomotive energy of individual microorganisms is transferred also carries interactions that drive the coherence. The concentration dependence of correlations in the collective state is probed here with a novel technique that herds bacteria into condensed populations of adjustable concentration. For the particular thin-film geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
652
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 668 publications
(702 citation statements)
references
References 17 publications
43
652
4
3
Order By: Relevance
“…Note that the collective swimming speed and vortex size are large enough that the Péclet number in these systems can also approach or even exceed unity, implying that flow-induced transport of chemical species can outcompete diffusion, even though at the single-cell level this is not the case. Subsequent experimental work on thin films (Sokolov et al 2007) has shown analogous behaviour, and further investigations of quasi-two-dimensional systems (Cisneros et al 2007Wensink et al 2012;Dunkel et al 2013b) have explored in more detail the nature of this 30 R. E. Goldstein mesoscale 'bacterial turbulence', and in particular the statistics of velocity distributions and correlation functions.…”
Section: Collective Behaviour In Microswimmer Suspensionsmentioning
confidence: 93%
“…Note that the collective swimming speed and vortex size are large enough that the Péclet number in these systems can also approach or even exceed unity, implying that flow-induced transport of chemical species can outcompete diffusion, even though at the single-cell level this is not the case. Subsequent experimental work on thin films (Sokolov et al 2007) has shown analogous behaviour, and further investigations of quasi-two-dimensional systems (Cisneros et al 2007Wensink et al 2012;Dunkel et al 2013b) have explored in more detail the nature of this 30 R. E. Goldstein mesoscale 'bacterial turbulence', and in particular the statistics of velocity distributions and correlation functions.…”
Section: Collective Behaviour In Microswimmer Suspensionsmentioning
confidence: 93%
“…However, the swimming characteristics of the individuals do have an effect: the morphology of a cell can induce complex flow fields, especially in constrained environments, and collective motion can arise (e.g. Sokolov et al, 2007) potentially adjusting effective mechanical properties of the suspension and influencing fluid-substrate interactions and dipersion of signal molecules.…”
Section: Morphologymentioning
confidence: 99%
“…actinidiae (PSA) is the 40 most important threat to the kiwifruit industry worldwide (Cameron & 45 PSA was first reported in Japan (1984) (Takikawa et al 1989); Korea (1989) (Koh et al 1994) 46 and; in the early 90's, in Italy (Scortichini 1994), although at that time the disease was highly 47 destructive in Japan and Korea, the consequences for the kiwifruit plants in Italy were no more 48 than leaf spot and twig dieback in some orchards (Cameron & 94 move toward a more favorable environment through swimming, which is the individual 95 movement of one bacterium, mainly driven by its flagella (Sokolov et al 2007). This movement 96 allows them to find and associate to more complex bacterial structures, forming multicellular 97 communities (Sokolov et al 2007;Verstraeten et al 2008). These surface-associated 98 multicellular communities are often used by bacteria because they give them several advantages 99 over the individual-cell mode, particularly regarding their resistance to stressful environmental 100 conditions or to chemical compounds (Verstraeten et al 2008).…”
Section: Introductionmentioning
confidence: 99%